World brotherhood colonies: A preview of Paramahansa Yogananda's understudied vision for communities founded upon the principles of yoga - Christopher P Miller (Wolters Kluwer Medknow Publications, 2018)
Paramahansa Yogananda (1893-1952) founded the Yogoda Satsanga Society (YSS) of India in 1917. With the blessings of his guru Sri Yukteswar, he then traveled to the United States in 1920 where he eventually established the American branch of the YSS known as the Self-Realization Fellowship to teach Kriyā-yoga and "original Christianity." Tracing the history of the World Brotherhood Colony movement as it made its way from India to America and back to India, this article shows how Yogananda's colonies today continue to provide a space for members of the growing global middle class to live a simpler life grounded in yogic principles. Scholars concerned with yoga's historical transmission and entrance into transnational practice will find this article useful for understanding the implications of Paramahansa Yogananda's World Brotherhood Colonies in the history of modern yoga.